THE IMPORTANCE OF LESSON PLANS FOR LECTURERS (Lecturers’ Perspective at STAI Syekh H Abdul Halim Hasan Al -Ishlahiyah Binjai) - Sari, Darmaida (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to find out how important preparing lesson plans for lecturers at STAI Syekh H Abdul Halim Hasan Al Ishlahiyah Binjai before teaching in the classrooms. This research is a descriptive qualitative study with 15 informants as participants. The data proved that all the Islamic education lecturers made and prepared lesson plans before they taught in the classrooms. They revealed that preparing lesson plans were very important to do before coming to the classrooms. They argued that professional lecturers are lecturers who can make good lesson plans that have clear learning objectives and outputs in accordance with the interests and talents of their students. The results from the interviews were also found that these lecturers also prioritized Islamic moral values aspects in their lesson plans. They said that lecturers who did not have lesson plans tended to teach haphazardly and aimlessly and had no output to produce. Lesson plan is the main and the crucial aspects that must be made and designed by the lecturers. Lecturers felt insecure and not free if they entered class without making and bringing lesson plans when they were in the classrooms. In supporting the suitability between the lesson plans made by the lecturers and what were taught in the classrooms, Quality Assurance Agency (LPM) of STAI Syekh H. Abdul Halim Hasan Al – Ishlahiyah Binjai always monitors and evaluates the learning activities of the lecturers at the end of the semester.